Yiqi Wenyang Jiedu prescription for preventing and treating postoperative recurrence and metastasis of gastric cancer: a randomized controlled trial protocol - Cao, Luchang; Zhu, Guanghui; Wang, Xinmiao; Kuang, Ziyu; Song, Xiaotong; Ma, Xinyi; Zhu, Xiaoyu; Gao, Ruike; Li, Jie (Frontiers in Oncology, 2024)
Introduction Postoperative recurrence and metastasis of gastric cancer (GC) are primary factors that contribute to poor prognosis. GC recurs at a rate of approximately 70%–80% within 2 years after local treatment and approximately 90% within 5 years. “Yang-deficient toxic node” is the core pathogenesis of GC recurrence and metastasis. The Yiqi Wenyang Jiedu prescription (YWJP), a form of complementary and alternative medicine in China, is an empirical remedy to prevent postoperative recurrence and metastasis of GC. Taking the main therapeutic principles of “nourishing Qi and warming Yang, strengthening Zhengqi, and detoxifying” can aid in preventing the recurrence and metastasis of GC in patients during the watchful waiting period after surgery and adjuvant chemotherapy. This approach aims to enhance the quality of life of patients. However, high-quality evidence to support this hypothesis is lacking. This study will aim to investigate the efficacy and safety of YWJP to prevent and treat postoperative metastasis and GC recurrence. Methods The study will be a multicenter, randomized, double-blind, placebo-parallel-controlled clinical trial. A total of 212 patients who completed adjuvant chemotherapy within 8 months of radical gastrectomy will be enrolled. Patients in the intervention group will receive the YWJP, whereas those in the control group will receive a placebo. The main outcome was the disease-free survival (DFS) rate 2 years after surgery. The secondary outcomes included DFS time, overall survival, annual cumulative recurrence and rate of metastasis after 1–3 years, cumulative annual survival after 1–3 years, fat distribution-related indicators, tumor markers, peripheral blood inflammatory indicators, prognostic nutritional index, symptoms and quality of life evaluation, medication compliance, and adverse reaction rate. Discussion There is a lack of effective therapy after the completion of adjuvant therapy during the postoperative period of watchful waiting. This study will be the first randomized clinical trial to evaluate whether complementary and alternative medical interventions can effectively prevent recurrence and metastasis during the watchful waiting period after GC surgery and to provide evidence for surveillance treatment management after GC surgery. Clinical trial registration ClinicalTrials.gov, identifier NCT05229809.